Examination Of Factors Determining Transfer Price In Indonesian Mining Companies - Rahman, Arief; Ernawati, Ernawati (E-Jurnal Akuntansi; Vol 32 No 5 (2022), 2022)
The purpose of this study was to examine the effect of firm size, leverage, tax planning, tunneling incentives, intangible assets, and multinationality on the decision to transfer pricing. The research was conducted on mining sector companies listed on the Indonesia Stock Exchange in 2015-2019 by applying multiple linier regression analysis. Samples were obtained by purposive sampling method. Based on the results of the hypotheses in this study, it shows that firm size, leverage, intangible assets, multinationality affect transfer pricing, whereas tax planning and tunneling incentives do not affect transfer pricing. The results have substantial implications for theory as well as practice, in understanding transfer pricing decision, particularly for mining companies.  Keywords: Transfer Pricing; Leverage; Intangible Assets; Multinationality.